Factors Predicting Interior Preferences for Vihara or Ubosot - Chumporn Moorapun; Kotchapong Lekhakul; Chanumpa Dechnitirat (My University, 2023)
Designers need to comprehend people's preferences to produce enjoyable environments. This research investigated how coherence, complexity, legibility, and mystery can anticipate the interior preferences of Vihara or Ubosot in various architectural styles. Forty-five students were taken to 19 temples and asked to complete an online survey. The findings revealed that coherence, legibility, and mystery were predictors of interior preferences, except for complexity. Moreover, coherence was the only predictor for the Sukhothai style, while coherence and mystery were predictors for the Ayutthaya style. On the other hand, all four variables predicted interior preferences for the Lanna style.
Keywords: Legibility; Urban Green Space and Health